Emp10 encodes a mitochondrial PPR protein that affects the cis‐splicing of nad2 intron 1 and seed development in maize. (4th May 2017) - Cai, Manjun; Li, Shuzhen; Sun, Feng; Sun, Qin; Zhao, Hailiang; Ren, Xuemei; Zhao, Yanxin; Tan, Bao‐Cai; Zhang, Zuxin; Qiu, Fazhan
Summary: In higher plants, many mitochondrial genes contain group II‐type introns that are removed from RNAs by splicing to produce mature transcripts that are then translated into functional proteins. However, the factors involved in the splicing of mitochondrial introns and their biological functions are not well understood in maize. Here, we isolated an empty pericarp 10 ( emp10 ) mutant and identified the underlying gene by map‐based cloning. Emp10 encodes a P‐type mitochondria‐targeted pentatricopeptide repeat (PPR) protein with 10 PPR motifs. Loss of Emp10 function results in splicing defect of the first intron of nad2, a gene encoding subunit 2 of NADH dehydrogenase (also called complex I). The emp10 mutant has undetectable activity of complex I and has arrested development of embryo and endosperm, and thus defective seeds with empty pericarp. Additionally, the basal endosperm transfer layer cells were severely affected, indicating the deficiency of cell wall ingrowths in the emp10 kernels. Moreover, the alternative respiratory pathway involving alternative oxidase was significantly induced in the emp10 mutant. These results suggest that EMP10 is specifically required for the cis ‐splicing of mitochondrial nad2 intron 1, embryogenesis and endosperm development in maize. Significance Statement: The analysis of maize mutants provides important physiological, genetic and mechanistic insights to what has been described in dicot plant species (predominantly in Arabidopsis thaliana ), with regard to group II intron splicing in 'high‐plant' organelles.